A Simulation Study of Drying Chamber for Marine Product - Mohd Rosli, Mohd Afzanizam; Hiew , Sit Jing; Mohd Azhar, Nur Izzati; Saputra, Maidi; Ali, Sulaiman (International Journal of Integrated Engineering, 2021)
Drying chamber is a drying application for agriculture product to produce high quality and hygiene product. The purpose of this paper is to propose best configuration trays arrangement in drying chamber for better distribution of velocity and temperature. Therefore, five configurations of trays are analyzed to obtain the best performance of uniformity air flow distribution within drying chamber. CFD simulation studied the uniform air flow in the drying chamber in steady state condition. A validation is performed by comparing the data obtained from the literature review CFD simulation to ensure the methodology is correct. Then, the drying chamber with different trays arrangements are simulated using CFD simulations to obtain velocity and temperature distributions at nine plotted points on trays. From the results obtained, it concluded that design (A) and (D) are selected as the best designs for uniformity because there is less discrepancy for each point contributed the more uniformity of distribution.